Multi-Level Moderation Of Hedonic Motives And Online Promotions In Strengthening The Connection Between E-Impulsive Purchase Tendency, Purchase Decisions And Consumer Satisfaction- Proposed Framework - Zulfikar, Rizka; Yulianti, Farida; Lamsah, Lamsah; Purboyo, Purboyo; Wicaksono, Teguh (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to propose a multi-level moderation framework for the role of hedonic motive (HM) variables and online promotion (OP) the connection between e-Impulsive Purchase Tendency (e-IPT) and Consumer Satisfaction (CS) mediated by e-Impulsive Purchase Decision (e-IPD). Some previous studies were mostly conducted to identify the initial condition of impulsive Purchase. While there is a lot of research on e-impulsive Purchase (e-IP), few have focused on the consequences of e-IPT, e-IPD and CS. Additionally, there is still little research on how HM and OP interact to affect how e-IP and CS are connected. Thus, e-IPD as a mediator in the connection between e-IPT and CS is still understudied. This study bridges this gap by examining the e-IPT as a mediator as well as HM and OP as a moderator with a multi-level moderation study. The purpose of this research is to aid shops who want to keep customers by offering more information about online purchases. To the best of our knowledge, not many studies have looked at how HM might moderate the connection between e-IPT, e-IPD, and CS. The investigation of tiered moderation in the interaction between HM and OP that will impact CS is the innovative aspect of this work. The pertinent data regarding e-IP will be supplemented by the moderated mediation model that has been created and tested here.